Challenges and Strategies in Learning News Anchoring: Insights from EFL Tertiary Students in Speaking Class - Anne Ratna, Suminar; Pratama , Naval Yoga (UIR Press, 2024)
This research aims to find out EFL tertiary students’ challenges and strategies in learning news anchoring in speaking class. Data were collected through two instruments including test and questionnaire with 24 participants taken as sample through purposive sampling technique. Test was used as instrument to categorize the sample into 8 high achievers, 8 middle achievers, and 8 low achievers. The research was a kind of descriptive research using Walizer’s (1990) formula to analyze the five-likert scaled questionnaire and the data were interpreted using descriptive quantitative method of analysis. The findings of the research revealed that the EFL tertiary students faced four challenges in learning news anchoring such as challenges in pronouncing some technical terms, challenges in speaking fast like a news anchor, challenges in memorizing the news script, and challenges in delivering news with news anchor-like intonation. Furthermore, the findings of the research also found six strategies mostly used by the students in learning news anchoring such as practising frequently alone at home, watching the news anchor video shared by the lecturer in the class, imitating the lecturer’s example of performing news anchor in the class, learning from lecturer’s explanation, watching news anchor on television and watching news anchor video on Youtube. Since high achievers were found to use more than one strategy in learning news anchoring, the present research recommended the students to use more than one strategy to succeed in learning to be news anchor in speaking class.